Mate Selection and reproductive success in the Amazonian angelfish, Pterophyllum scalare (Osteichthyes: Cichlidae) - Chellappa, Sathyabama; Cacho, Maria do Socorro Ribeiro Freire; Volpato, Gilson Luiz [UNESP] (My University, 2014)
Mate selection and mating success in the Amazonian angelfish, Pterophyllum scalare were experimentally investigated in the laboratory. This species has a breeding system where male body size and substrate type could be decisive for mate selection by females. The aims of this study were to identify the male traits contributing to reproductive success, and to evaluate preferences for each male trait and their relative importance for the females. Different types of Amazonian aquatic vegetation were provided as potential spawning substrates, which were selected and defended by males with varying levels of aggression. Laboratory observations revealed that large sized males were aggressive, dominant and involved in agonistic interactions attacking intermediate and small sized males. Body size and dominance of males were related to space use and proximity to potential spawning sites. The female assessed the male based on two important traits: the type of spawning substrate and the body size. The quality of the territory is the most important trait for females to choose the mate. The larger males defending low quality spawning substrate (aquatic plants with narrow and small leaves) were discriminated against smaller males defending good quality spawning substrate (aquatic plants with broad leaves, Anubia sp. and Echinodorus amazonensis). Female preference for substrate type was independent of male body size. When given a choice between males matched for size but differing in the type of substrates defended, females preferred the male defending good quality spawning substrate. When substrate type was held constant females preferred larger males. Though both traits may be strong predictors of the male's competitive ability, the substrate type was the main determinant of male reproductive success.
Keywords: Amazoniancichlid fish; Female mate preference; Male mating success; Pterophyllum scalare